Prototype Sistem Kontrol Otomatis pada Sterilizer Berbasis Arduino UNO R3 - Ahmad Mahfud (JURNAL CITRA WIDYA EDUKASI, 2022)
A sterilizer is a pressurized steam vessel used to boil oil palm fruit. The effective boiling process greatly determines the quality of the boiled fruit, as well as the effectiveness of extracting oil from the fruit flesh. Setting the stages of opening and closing the inlet valve, exhaust valve and condensate valve, greatly affects the quality of the product. The formation of the triple peak pattern needed to get the best results is formed from the operational settings of the three valves through 9 steps with a very short time duration. The manual operation of the sterilizer clearly has a less effective impact on the performance of the sterilizer. The Sterilizer prototype was designed in the context of researching the Arduino UNO application to support an automatic control system for 3 valve units (inlet, exhaust and condensate) so that they can operate following predetermined cycles and stages. As well as the convenience of monitoring the rate of change of air pressure in the cooking tube, through the LCD monitor device. The results showed that the use of Arduino UNO as a controller in controlling the performance of the Inlet Valve, Exhaust Valve and Condensate Valve could be done well. Monitor display that displays the rate of change of pressure based on the embedded pressure sensor, can be monitored properly. The maximum pressure applied to the protorype tube sterilizer is 1.4 bar. With an interval of 1 boiling cycle for 87 seconds.